GAMBARAN KETUBAN PECAH DINI DI RSUP PROF DR. R. D. KANDOU MANADO - Lowing, Joshua G. A.; Lengkong, Rudy; Mewengkang, Maya (e-CliniC, 2015)
Abstract: Premature rupture of membrane (PROM) is the rupture of fetal membrane before labor. It is assumed that the membrane rupture is related to biochemical changes of the extracellular collagen matrix of amnion and chorion as well as apoptosis of the fetal membrane. This was a descriptive retrospective study. Data were obtained from the medical record of the Department of Obstetrics and Gynecology Department, Prof. Dr. R. D. Kandou Hospital Manado. The results showed that during the period of 1 January - 31 December 2013 there were 3,810 labors; 59 cases (1.54%) of PROM. Viewed from the position of fetus in utero and the duration of pregnancy, most of the fetus had cephalic presentation and most of the pregnancies were aterm. There was no mortality during the period.Keywords: PROMAbstrak: Ketuban pecah dini (KPD) merupakan keadaan pecahnya selaput ketuban sebelum persalinan. Pecahnya selaput ketuban diduga berkaitan dengan perubahan proses biokimiawi yang terjadi dalam matriks kolagen ekstrasel amnion dan korion serta apoptosis membran janin. Penelitian ini menggunakan metode retrospektif deskriptif. Data diambil dari rekam medik Bagian Obstetri Ginekologi RSUP. Prof. Dr. R. D. Kandou Manado. Selama periode 1 Januari 2013 - 31 Desember 2013 tercatat 3.810 persalinan dengan 59 kasus KPD (1,54%). Dilihat dari segi letak janin dan usia kehamilan, sebagian besar janin dengan letak kepala dan usia kehamilan rata-rata aterm. Mortalitas tidak ditemukan.Kata kunci: ketuban pecah dini